EUROPEAN CREDIT-TRANSFER SYSTEM AND EUROPEAN SPACE OF HIGHER EDUCATION - Sharbenko, T.V. (World of Medicine and Biology, 2010)
Loading must not be based exceptionally on contact watches. It engulfs all of types of educational activity, necessary for achievement of the expected results inclusive in course of time, spent on: independent work, obligatory production practice, preparation for an evaluation, time necessity on an own evaluation. Determination of loading must be constantly regulated through monitoring and feed-back with students (review of students through a questionnaire). All of these instruments, and also application of the credit-module system of organization of educational process, will approach our state to the entry in European educational space.